Cancer Screening Among Rural and Urban Clinics During COVID-19: A Multistate Qualitative Study. Issue 6 (7th June 2022) - Hanna, Karim; Arredondo, Brandy L.; Chavez, Melody N.; Geiss, Carley; Hume, Emma; Szalacha, Laura; Christy, Shannon M.; Vadaparampil, Susan; Menon, Usha; Islam, Jessica; Hong, Young-Rock; Alishahi Tabriz, Amir; et al.
Abstract : PURPOSE: The effects of COVID-19 have been understudied in rural areas. This study sought to (1) identify cancer screening barriers and facilitators during the pandemic in rural and urban primary care practices, (2) describe implementation strategies to support cancer screening, and (3) provide recommendations. METHODS: A qualitative study was conducted (N = 42) with primary care staff across 20 sites. Individual interviews were conducted through videoconference from August 2020 to April 2021 and recorded, transcribed, and analyzed using deductive and inductive coding (hybrid approach) in NVivo 12 Plus. Practices included federally qualified health centers, tribal health centers, rural health clinics, hospital/health system–owned clinics, and academic medical centers across 10 states including urban (55%) and rural (45%) sites. Staff included individuals serving in the dual role of health care provider and administrator (21.4%), health care administrator (23.8%), physician (19.0%), advanced practice provider (11.9%), or resident (23.8%). The interviews assessed perceptions about cancer screening barriers and facilitators, implementation strategies, and future recommendations. RESULTS: Participants reported multilevel barriers to cancer screening including policy-level (eg, elective procedure delays), organizational (eg, backlogs), and individual (eg, patient cancellation). Several facilitators to screening were noted, such as home-based testing, using telehealth, and strong partnerships with referral sites. Practices used strategies to encourage screening, such as incentivizing patients and providers and expanding outreach. Rural clinics reported challenges with backlogs, staffing, telehealth implementation, and patient outreach. CONCLUSION: Primary care staff used innovative strategies during the pandemic to promote cancer screening. Unresolved challenges (eg, backlogs and inability to implement telehealth) disproportionately affected rural clinics. Abstract :